Time-varying emission of electrons and its relevant EM phenomenon - Liu, Yangjie (2014)
The main-body of this thesis or dissertation attempts to consider two aspects of electron emission scenario: one on increasing electron emission counts by injecting time-varying electron flow under short-pulse condition and the other on induced electromagnetic fields by electron flow within space.